Genome Editing with Engineered Nucleases in Economically Important Animals and Plants: State of the Art in the Research Pipeline - Sovová, Tereza; Kerins, Gerard; Demnerová, Kateřina; Ovesná, Jaroslava (Current issues in molecular biology, 2017)
After induced mutagenesis and transgenesis, genome editing is the next step in the development of breeding techniques. Genome editing using site-directed nucleases - including meganucleases, zinc-finger nucleases (ZFNs), transcription activator-like effector nucleases (TALENs), and the CRISPR/Cas9 system - is based on the mechanism of double strand breaks. The nuclease is directed to cleave the DNA at a specific place of the genome which is then repaired by natural repair mechanisms. Changes are introduced during the repair that are either accidental or can be targeted if a DNA template with the desirable sequence is provided. These techniques allow making virtually any change to the genome including specific DNA sequence changes, gene insertion, replacements or deletions with unprecedented precision and specificity while being less laborious and more straightforward compared to traditional breeding techniques or transgenesis. Therefore, the research in this field is developing quickly and, apart from model species, multiple studies have focused on economically important species and agronomically important traits that were the key subjects of this review. In plants, studies have been undertaken on disease resistance, herbicide tolerance, nutrient metabolism and nutritional value. In animals, the studies have mainly focused on disease resistance, meat production and allergenicity of milk. However, none of the promising studies has led to commercialization despite several patent applications. The uncertain legal status of genome-editing methods is one of the reasons for poor commercial development, as it is not clear whether the products would fall under the GMO regulation. We believe this issue should be clarified soon in order to allow promising methods to reach their full potential.
Keywords: zinkové prsty; Disease Resistance; Genome, Plant; odolnost vůči nemocem; editace genu; Plants, Genetically Modified; endonukleasy; genom rostlinný; Zinc Fingers; Gene Editing; Animals, Genetically Modified; zemědělské plodiny; Crops, Agricultural; genetické inženýrství; zvířata; geneticky modifikované rostliny; geneticky modifikovaná zvířata; Genetic Engineering; Endonucleases; Animals